2005
DOI: 10.1161/01.str.0000157598.02014.37
|View full text |Cite
|
Sign up to set email alerts
|

α 1 -Antichymotrypsin Gene ( SERPINA3 ) A/T Polymorphism as a Risk Factor for Aneurysmal Subarachnoid Hemorrhage

Abstract: Background and Purpose-The member 3 of clade A of serine proteinase inhibitors (SERPINA3), known previously as the ␣ 1 -antichymotrypsin, is an acute phase protein, the levels of which increase in acute and chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 33 publications
1
15
1
2
Order By: Relevance
“…The results of the first screening of 147 FIA patients and 139 controls showed a weak significance (p = 0.037) leaning towards a result similar to that described by Slowik et al [2] (p = 0.009) for the genotype model AA versus AT + TT. This encouraged us to proceed by increasing the cohort sizes and, in correlation with the previous report [2], to focus on patients who had suffered a rupture of an IA.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…The results of the first screening of 147 FIA patients and 139 controls showed a weak significance (p = 0.037) leaning towards a result similar to that described by Slowik et al [2] (p = 0.009) for the genotype model AA versus AT + TT. This encouraged us to proceed by increasing the cohort sizes and, in correlation with the previous report [2], to focus on patients who had suffered a rupture of an IA.…”
Section: Resultssupporting
confidence: 75%
“…Slowik et al [2] found the A15T polymorphism of the SERPINA3 gene to be associated with the risk factor for aneurysmal subarachnoid hemorrhage (SAH) in 180 Polish patients as compared to 263 controls. This polymorphism has been described to be associated with Alzheimer’s disease [3], primary intracerebral hemorrhage [4, 5] and poststroke dementia [6].…”
Section: Introductionmentioning
confidence: 99%
“…A single nucleotide polymorphism (SNP) (rs4934) is located in the signal peptide region (at codon 15) in exon 2. It has been postulated that this genotype affects the expression of serpinA3 protein (12)(13)(14). Moreover, studies have proven that this genetic variant is a risk factor for aneurysmal subarachnoid hemorrhage in a Polish (12), but not in a Chinese (13) or Japanese (14) population.…”
Section: Introductionmentioning
confidence: 99%
“…Επιπλέον, συμμετέχει στη συσσώρευση και την ενεργοποίηση των αιμοπεταλίων, καθώς και στη διάσπαση των παραγόντων πήξης και των πρωτεϊνών της εξωκυττάριας θεμέλιας ουσίας (193). Όλες αυτές οι δράσεις της cat G πιθανόν να καθιστούν το αγγειακό τοίχωμα πιο εύθραυστο και επιρρεπές σε αιμορραγικά γεγονότα (238).…”
Section: Il-1α(-889)unclassified
“…Το Τ αλληλόμορφο του ACT πολυμορφισμού βρέθηκε ότι αυξάνει τον κίνδυνο εμφάνισης ανευρυσματικής υπαραχνοειδούς αιμορραγίας. Η συσχέτιση αυτή αποδόθηκε στην επίδραση της ACT στην αναδιάρθρωση του τοιχώματος των αγγείων και στις φλεγμονώδεις διεργασίες, τα οποία διέπουν το σχηματισμό ανευρυσμάτων (238).…”
Section: Il-1α(-889)unclassified